What attracts listeners to Web radio? A case study from Germany. (1st October 2013) - Stark, Birgit; Weichselbaum, Philipp
With the advent of Web radio in a changing media environment, radio has once more reinvented itself in terms of both scope (emerging new forms such as online-only radio) and listening experience (interactivity, personalization and content modularization). Scholars have identified these technological changes as evidence for an evolving radio. The audience perspective, however, has been researched far less. We go beyond existing studies and are interested in the role signature features of Web radio play for its listeners. We answer two research questions: (1) What do users expect from listening to Web radio as an interactive medium? (2) What are the gratifications sought when tuning in to Web radio in comparison to offline radio? The research is based on an exploratory online survey among Web radio listeners in Germany. Our findings show that interactive Web radio features play only a minor role for listeners. Instead, they focus on music. When compared to other online media, listening to Web radio is ranked highest among affective gratification items. We discuss theoretical and practical implications of our findings, as well as Web radio's potential impact on traditional radio.